A global view of regulatory ecosystem services: existed knowledge, trends, and research gaps - Mengist, Wondimagegn; Soromessa, Teshome; Feyisa, Gudina Legese (Ecological processes, 2020)
Ecosystem services (ES) are growing fields of research. It helps to provide an inherent way to understand the synergy and trade-offs between human beings and their natural environment. Regulatory ecosystem services (RES) are significantly important to maintaining the world in which people can live, and control the negative effects of flood, disasters, and diseases. It can also provide regulatory services like ecosystem protection, human safety, and the provision of other ES. However, emerging ES decision-making agendas focus on ES that is tangible and has a direct link with human well-being. Thus, the attention given to RES is low due to its less tangible benefits and complexity to measure the benefits. Disregarding and lack of attention from policymakers and scientific community may lead to unintended risks to human well-being and significant influences on the provision of other ES. This study describes the research trends on RES, knowledge generated, and the major limitation. We concluded that though there is an exponential growth of scientific publications on ES, no adequate studies were found on RES. Also, the existed studies varied in their size and types of RES indicators covered, habitats/ecosystems, and geographic extent addressed. There was also a lack of connecting knowledge generated on the benefits of RES with the national policy of natural resource management, inconsistency of ES classification, and methodological diversity. Therefore, scientific communities are promoted to link RES studies with human health. Besides, the researcher should give priority for the least studied ecosystems and its services, developing robust methodology, and proposing management options to enhance the regulatory services of ecosystems.